Lacteal junction zippering protects against diet-induced obesity - Zhang, Feng; Zarkada, Georgia; Han, Jinah; Li, Jinyu; Dubrac, Alexandre; Ola, Roxana; Genet, Gael; Boyé, Kevin; Michon, Pauline; Künzel, Steffen E.; Camporez, Joao Paulo; Singh, Abhishek K.; et al. (Science (American Association for the Advancement of Science), 2018)
Chylomicrons are specialized particles that carry dietary fats from the intestine to the bloodstream for absorption into the body. Lacteals are lymphatic vessels that act as the highway for chylomicron transport, but it is unclear how passage occurs. Zhang et al. report that two endothelial cell receptors, neuropilin-1 (NRP1) and vascular endothelial growth factor receptor 1 (VEGFR1, also known as FLT1), are required to convert the entry spaces between lacteals from open junctions to closed, zipped structures (see the Perspective by McDonald). Mice that were fed a high-fat diet were subsequently rendered resistant to weight gain if NRP1 and FLT1 were inactivated. Science , this issue p. 599 ; see also p. 551 Preventing chylomicron uptake by deletion of endothelial receptors makes mice resistant to obesity. Excess dietary lipid uptake causes obesity, a major global health problem. Enterocyte-absorbed lipids are packaged into chylomicrons, which enter the bloodstream through intestinal lymphatic vessels called lacteals. Here, we show that preventing lacteal chylomicron uptake by inducible endothelial genetic deletion of Neuropilin1 ( Nrp1 ) and Vascular endothelial growth factor receptor 1 ( Vegfr1 ; also known as Flt1 ) renders mice resistant to diet-induced obesity. Absence of NRP1 and FLT1 receptors increased VEGF-A bioavailability and signaling through VEGFR2, inducing lacteal junction zippering and chylomicron malabsorption. Restoring permeable lacteal junctions by VEGFR2 and vascular endothelial (VE)–cadherin signaling inhibition rescued chylomicron transport in the mutant mice. Zippering of lacteal junctions by disassembly of cytoskeletal VE-cadherin anchors prevented chylomicron uptake in wild-type mice. These data suggest that lacteal junctions may be targets for preventing dietary fat uptake.